PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN HOTEL SWISS-BELINN MAKASSAR - Rakasiwi, Fajar (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research was to find out the influence of organizational culture and competence partially and simultaneously on employee performance. This research using quantitative research methods with techniques of data collecting through spreading of questioner and supported secondary data. Data analysis method used is multiple regression analysis. The sample in this research is a simple random sampling. The number of samples is 81 respondents from employees of Swiss-Belinn Hotel Makassar at the head office. The results of this research show that the variables of organizational culture and competence partially and simultaneously have a significant influence on the performance of employees of Swiss-Belinn Hotel Makassar at the head office. Employee performance variables can be explained by the variables of organizational culture and competence by 66.8%. While the remaining at 33.2% is explained by other variables not included in this research.